Tinjauan Mediasi Sebagai Alternatif Penyelesaian Sengketa Pengakuan Anak Luar Nikah Perspektif Hukum Keluarga Islam - Taufiqurrahman, Muh.; Musleh Harry (Kartika: Jurnal Studi Keislaman, 2025)
Disputes over the recognition of children born out of wedlock are complex issues because they involve fundamental differences between Islamic law, which stipulates that a child's lineage is only connected to the mother and her family, and positive law after Constitutional Court Decision No. 46/PUU-VIII/2010, which opens up the possibility of civil relations with the biological father. This study aims to analyze mediation as an alternative to resolving disputes over the recognition of children born out of wedlock from the perspective of Islamic family law. The method used in this study is library research. The results of this study explain that from the perspective of Islamic family law, dispute resolution prioritizes the values of islah (peace), deliberation, and family welfare. The principles of maqasid syariah, such as preserving lineage (ḥifẓ al-nasl), protecting life (ḥifẓ al-nafs), and preserving honor ('irdh), place peace as the most important path. Therefore, mediation is the method most in line with the ethics of conflict resolution in Islam. Mediation also has formal legal force through PERMA No. 1 of 2016, and the results can be recorded in a legally binding peace agreement, thus providing legal certainty for the parties. Thus, mediation is the most appropriate and humane way to resolve disputes over the recognition of children born out of wedlock, as it combines Islamic family law values with positive legal certainty for the protection of children